Distribution. W Europe from Atlantic coast E in Cricetidae ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Distribution. W Europe from Atlantic coast E to Yenisei River, N border set by Arctic tundra and S border frequently coincides with mountain ranges: Pyrenees, Alps, Apennines, and Balkan in S Europe, Pontic Mts in Anatolia, and Altai and Sayan Mts in C Asia; widespread on islands offshore Atlantic and Baltic coasts. Introduced to SW Ireland. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 302, DOI: 10.5281/zenodo.6707142 ...